Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1108/jmtm-10-2019-0368
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Industry 4.0 implementation on supply chains

Abstract: PurposeThe study aims to analyse the impact of Industry 4.0 implementation on supply chains and develop an implementation framework by considering potential drivers and barriers for the Industry 4.0 paradigm.Design/methodology/approachA critical literature review is performed to explore the key drivers and barriers for Industry 4.0 implementation under four business dimensions: strategic, organisational, technological and legal and ethical. A system dynamics model is later developed to understand the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
239
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(300 citation statements)
references
References 47 publications
9
239
0
9
Order By: Relevance
“…The application of the 4.0 enabling technologies tends to enhance the entire supply chain performance, especially in terms of the procurement, manufacturing, inventory management, and trading, while also promoting the concept of information sharing and automation, digitization, and transparency across the supply network ( Factorachian and Kazemi, 2020 ). Ghadge et al. (2020) emphasized the need to integrate the digital businesses, with digital supply chains, such as the incorporation and adoption of the (i) digital culture, (ii) new digital business models, (iii) optimized data management, (iv) connected processes and devices, (v)integrated performance management, (vi) synchronized planning and inventory management, (vii) supply chain transparency, (viii) integrated value chains, (ix) connected customers and channels, and the (x) collaboration and data sharing for fruitful adoption towards the concept of industry 4.0.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The application of the 4.0 enabling technologies tends to enhance the entire supply chain performance, especially in terms of the procurement, manufacturing, inventory management, and trading, while also promoting the concept of information sharing and automation, digitization, and transparency across the supply network ( Factorachian and Kazemi, 2020 ). Ghadge et al. (2020) emphasized the need to integrate the digital businesses, with digital supply chains, such as the incorporation and adoption of the (i) digital culture, (ii) new digital business models, (iii) optimized data management, (iv) connected processes and devices, (v)integrated performance management, (vi) synchronized planning and inventory management, (vii) supply chain transparency, (viii) integrated value chains, (ix) connected customers and channels, and the (x) collaboration and data sharing for fruitful adoption towards the concept of industry 4.0.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this regard, escalating the information exchange with the synchronization into the operations among supply chain partners, allows for the agility, efficiency, and total cost reduction throughout the entire supply network ( Ghobakhloo and Fathi, 2019 ). The model suggested by Ghadge et al. (2020) found that the cloud technology and RFID enhanced the operational efficiencies through a reduction in the inventory levels and the costs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Asset tracking and condition visibility is also difficult because few standards or metrics have been assessed in global logistics systems, particularly when new technology such as UAS is introduced ( Biton et al, 2019 ; Reyes et al, 2020 ; Ghadge et al, 2020 ). This research addresses this gap and describes the integration of a UAS in a global logistics system, and the metrics used to assess the integrated system.…”
Section: Introductionmentioning
confidence: 99%
“…‫ػورر‬ ‫ي‬ ‫ػث‬ ‫حي‬ ‫الخانة،‬ ‫تشيف‬ ‫البموؾ‬ ‫أو‬ ‫التحال‬ ‫ذات‬ ‫تشيف‬ ‫البموؾ‬ ‫مف‬ ‫نوع‬ ‫يد‬ ‫التور‬ ‫سمسمة‬ ‫اعتبار‬ ‫يموف‬ ‫ػمة‬ ‫سمس‬ ‫ػى‬ ‫ر‬ ‫ػارؾ‬ ‫مش‬ ‫ػل‬ ‫لك‬ ‫يموف‬ ‫حيث‬ ‫بو،‬ ‫الخاص‬ ‫األذف‬ ‫مستوى‬ ‫عمى‬ ‫بناء‬ ‫مشارؾ‬ ‫لكل‬ ‫رؤية‬ ‫تشيف‬ ‫البموؾ‬ ‫ػ‬ ‫ػ‬ ‫وج‬ ‫ػاكف‬ ‫ػ‬ ‫ام‬ ‫ػة‬ ‫ػ‬ ‫ر‬ ‫ومعر‬ ‫ػد‬ ‫ػ‬ ‫ي‬ ‫التور‬ ‫ػمة‬ ‫ػ‬ ‫سمس‬ ‫ػالؿ‬ ‫ػ‬ ‫خ‬ ‫ػف‬ ‫ػ‬ ‫م‬ ‫ػديميا‬ ‫ػ‬ ‫تق‬ ‫ػاء‬ ‫ػ‬ ‫أثن‬ ‫ػائع‬ ‫ػ‬ ‫البع‬ ‫ػدـ‬ ‫ػ‬ ‫تق‬ ‫ػدي‬ ‫ػ‬ ‫م‬ ‫ػة‬ ‫ػ‬ ‫رؤي‬ ‫ػد‬ ‫ػ‬ ‫ي‬ ‫التور‬ ‫ػور‬ ‫ػ‬ ‫وعب‬ ‫ود‬ ‫ألى‬ ‫ػف‬ ‫ػ‬ ‫ػ‬ ‫يمو‬ ‫ال‬ ‫ػا‬ ‫ػ‬ ‫ػ‬ ‫وم‬ ‫ػحف.‬ ‫ػ‬ ‫ػ‬ ‫بالش‬ ‫ػة‬ ‫ػ‬ ‫ػ‬ ‫الخان‬ ‫ػتندات‬ ‫ػ‬ ‫ػ‬ ‫المس‬ ‫ػرض‬ ‫ػ‬ ‫ػ‬ ‫وع‬ ‫ػة،‬ ‫ػ‬ ‫ػ‬ ‫الجمروي‬ ‫ػائ‬ ‫ػ‬ ‫ػ‬ ‫الوث‬ ‫ػة‬ ‫ػ‬ ‫ػ‬ ‫حال‬ ‫ػد‬ ‫ػ‬ ‫ػ‬ ‫وتحدي‬ ‫ػات،‬ ‫ػ‬ ‫ػ‬ ‫الحاوي‬ ‫ػحة‬ ‫ن‬ ‫ػى‬ ‫عم‬ ‫اؼ‬ ‫ػر‬ ‫االط‬ ‫ػة‬ ‫وار‬ ‫ػاع‬ ‫اجم‬ ‫دوف‬ ‫أخرى‬ ‫بسجالت‬ ‫و‬ ‫إلحا‬ ‫حتى‬ ‫أو‬ ‫حذرو‬ ‫أو‬ ‫سجل‬ ‫أى‬ ‫تعديل‬ ‫طرؼ‬ ‫المعامالت‬ (O'leary,2017) . ‫ا‬ ‫ػة‬ ‫ػ‬ ‫ػ‬ ‫وتقني‬ ‫ػناعة‬ ‫ػ‬ ‫ػ‬ ‫لمن‬ ‫ػع‬ ‫ػ‬ ‫ػ‬ ‫اب‬ ‫الر‬ ‫ػل‬ ‫ػ‬ ‫ػ‬ ‫الجي‬ ‫ػات‬ ‫ػ‬ ‫ػ‬ ‫تقني‬ ‫ػ‬ ‫ػ‬ ‫ػ‬ ‫تطبي‬ ‫ػ‬ ‫ػ‬ ‫ػ‬ ‫يتطم‬ ‫ػذا‬ ‫ػ‬ ‫ػ‬ ‫ل‬ ‫ػة‬ ‫ػ‬ ‫ػ‬ ‫مي‬ ‫ر‬ ‫ػد‬ ‫ػ‬ ‫ػ‬ ‫ي‬ ‫تور‬ ‫ػمة‬ ‫ػ‬ ‫ػ‬ ‫سمس‬ ‫ػود‬ ‫ػ‬ ‫ػ‬ ‫وج‬ ‫ػيف‬ ‫ػ‬ ‫ػ‬ ‫تش‬ ‫ػوؾ‬ ‫ػ‬ ‫ػ‬ ‫لبم‬ ‫(مؤتمتو)‬ digital supply chain ‫ػة‬ ‫الكامم‬ ‫ػفارية‬ ‫بالش‬ ‫يتسـ‬ ً ‫تماما‬ ً ‫متكامال‬ ً ‫نظاما‬ ‫يد‬ ‫التور‬ ‫سمسمة‬ ‫يجعل‬ ‫مما‬ ، ‫ػائى‬ ‫ػ‬ ‫الني‬ ‫ػت‬ ‫ػ‬ ‫المن‬ ‫ػميـ‬ ‫ػ‬ ‫بتس‬ ً ‫ػاءا‬ ‫ػ‬ ‫نتي‬ ‫ا‬ ‫و‬ ‫ػات‬ ‫ػ‬ ‫الموون‬ ‫و‬ ‫ػاـ‬ ‫ػ‬ ‫الخ‬ ‫اد‬ ‫ػو‬ ‫ػ‬ ‫الم‬ ‫ػوردى‬ ‫ػ‬ ‫م‬ ‫ػف‬ ‫ػ‬ ‫م‬ ً ‫ػدءا‬ ‫ػ‬ ‫ب‬ ‫ػد‬ ‫ػ‬ ‫ي‬ ‫التور‬ ‫ػمة‬ ‫ػ‬ ‫سمس‬ ‫اؼ‬ ‫ػر‬ ‫ػ‬ ‫أط‬ ‫ػع‬ ‫ػ‬ ‫لجمي‬ ‫ػل‬ ‫لمعمي‬(Schrauf and Berttam,2017;Ghadge et al, 2020;Nasiri et al, 2020) . ‫ػة‬ ‫ػ‬ ‫لتمبي‬ ‫ػة‬ ‫ػ‬ ‫التنظيمي‬ ‫ػة‬ ‫ػ‬ ‫الثقار‬ ‫و‬ ‫ػاؿ‬ ‫ػ‬ ‫األعم‬ ‫ػات‬ ‫ػ‬ ‫لعممي‬ ‫ػى‬ ‫ػ‬ ‫م‬ ‫الر‬ ‫ػوؿ‬ ‫ػ‬ ‫التح‬ ‫ػالؿ‬ ‫ػ‬ ‫خ‬ ‫ػف‬ ‫ػ‬ ‫م‬ ‫ػة‬ ‫ػ‬ ‫مي‬ ‫الر‬ ‫ػد‬ ‫ػ‬ ‫ي‬ ‫التور‬ ‫ػمة‬ ‫ػ‬ ‫سمس‬ ‫ػاء‬ ‫ػ‬ ‫بن‬ ‫ػتـ‬ ‫ػ‬ ‫وي‬ ‫ػت‬ ‫ػ‬ ‫ػ‬ ‫ن‬ ‫االنتر‬ ‫ػالؿ‬ ‫ػ‬ ‫ػ‬ ‫خ‬ ‫ػف‬ ‫ػ‬ ‫ػ‬ ‫م‬ ‫ػات‬ ‫ػ‬ ‫ػ‬ ‫المعموم‬ ‫ػع‬ ‫ػ‬ ‫ػ‬ ‫لجم‬ ‫ػة‬ ‫ػ‬ ‫ػ‬ ‫الذوي‬ ‫ػا‬ ‫ػ‬ ‫ػ‬ ‫التكنولوجي‬ ‫ػتخداـ‬ ‫ػ‬ ‫ػ‬ ‫اس‬ ‫ػى‬ ‫ػ‬ ‫ػ‬ ‫إل‬ ‫ػارة‬ ‫ػ‬ ‫ػ‬ ‫باالع‬ ‫ػوؽ،‬ ‫ػ‬ ‫ػ‬ ‫الس‬ ‫ػات‬ ‫ػ‬ ‫ػ‬ ‫متطمب‬ (Nasiri et al, 2020 ) ‫اسة‬ ‫در‬ ‫أشارت‬ .…”
unclassified